PRICING IN REINSURANCE BARGAINING WITH COMONOTONIC ADDITIVE UTILITY FUNCTIONS. Issue 2 (8th April 2016) - Boonen, Tim J.; Tan, Ken Seng; Zhuang, Sheng Chao
Abstract: Optimal reinsurance indemnities have widely been studied in the literature, yet the bargaining for optimal prices has remained relatively unexplored. Therefore, the key objective of this paper is to analyze the price of reinsurance contracts. We use a novel way to model the bargaining powers of the insurer and reinsurer, which allows us to generalize the contracts according to the Nash bargaining solution, indifference pricing and the equilibrium contracts. We illustrate these pricing functions by means of inverse- S shaped distortion functions for the insurer and the Value-at-Risk for the reinsurer.